2013
DOI: 10.4238/2013.march.11.6
|View full text |Cite
|
Sign up to set email alerts
|

Roles of functional NFKB1 and βTrCP insertion/deletion polymorphisms in mRNA expression and epithelial ovarian cancer susceptibility

Abstract: ABSTRACT. Epithelial ovarian cancer (EOC) is the leading cause of death among all gynecological cancers. Nuclear factor-kappa B (NF-κB) is involved in carcinogenesis and in the development of EOC. The β-transducin repeat-containing protein (β-TrCP) is a positive regulator of the NF-κB signaling pathway. Recent studies have indicated that the -94 ins/del ATTG polymorphism in the promoter region of the NFKB1 gene, and the 9N ins/del polymorphism in the 3ꞌ-untranslated region of the β-TrCP gene are associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
(40 reference statements)
6
12
0
Order By: Relevance
“…With respect to the β-TrCP 9-bp polymorphism, we did not find any association between this INS/DEL polymorphism and risk of BC. In accordance with our data, this variation has not been associated with the risk of epithelial ovarian cancer (EOC) (Huo et al, 2013). In contrast, this polymorphism was shown to be correlated with the susceptibility to hepatocellular carcinoma in Chinese (Chen et al, 2010).…”
Section: Genotypessupporting
confidence: 86%
See 1 more Smart Citation
“…With respect to the β-TrCP 9-bp polymorphism, we did not find any association between this INS/DEL polymorphism and risk of BC. In accordance with our data, this variation has not been associated with the risk of epithelial ovarian cancer (EOC) (Huo et al, 2013). In contrast, this polymorphism was shown to be correlated with the susceptibility to hepatocellular carcinoma in Chinese (Chen et al, 2010).…”
Section: Genotypessupporting
confidence: 86%
“…Association of 9-bp INS/DEL polymorphism in β-TrCP with β-TrCP mRNA expression has been reported. The presence of the 9-bp insertion allele in the 3′-UTR of β-TrCP has been shown to disrupt miR-920 binding, leading to relatively higher β-TrCP levels (Huo et al, 2013). Therefore, given the pivotal roles of p53, and β-TrCP proteins in the molecular pathology of tumorigenesis, the present study was aimed to evaluate the possible associations among three functional INS/DEL polymorphisms in the β-TrCP (9-bp) and TP53 (16-bp) genes and susceptibility to BC in an Iranian population.…”
Section: Introductionmentioning
confidence: 99%
“…Our results provide direct evidence that a genetic change in NFKB1 is linked to ovarian cancer in humans, and extend the list of variants that may affect the development of ovarian cancer (Huo et al, 2013).…”
Section: Discussionsupporting
confidence: 62%
“…Individuals with the ATTG2 allele (insertion) had a 1.367-fold risk of ovarian cancer compared with non-carriers. Interestingly, the study by Huo et al (2013) demonstrated that the mRNA level of NFKB1 in EOC tissues significantly correlated with the -94 insertion/deletion ATTG genotype; the highest level of NFKB1 was observed in EOC ATTG2 homozygous tissues. This correlation may be associated with the enhanced expression and activity of p50.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation